Video in the Age of Digital Learning - Köster, Jonas (Springer International Publishing, 2018)
Although video is now ubiquitous in education, its full potential is oftentimes not fully understood, nor is it used to utmost potential. This timely volume seeks to address this gap by providing educators and instructional designers with a comprehensive and in-depth understanding of video production processes and methods for designing effective instructional videos. From its discussion of the significance of digital learning and impact of instructional video to its unique focus on the best design and production techniques that make video an effective teaching tool, this book offers applicable and tested strategies for creating quality instructional video. The accompanying website, which allows readers to see sample videos and access additional online resources, underscores the book's practitioner focus. Among the topics covered: · Instructional videos for teaching and learning · Design and interactivity of instructional videos · Production, distribution, and integration of instructional videos · The future of instructional video Video in the Age of Digital Learning is an important, practical contribution to the scholarship exploring methods for sharing and acquiring knowledge in the digital age. It promises to be a valuable resource for educators, instructional designers, instructional media producers, and educational technology professionals.